SISTEM MONITORING PERBAIKAN MESIN PRODUKSI BERBASIS WEBSITE DENGAN PELAPORAN REALTIME - Danindra Irvanto; Suryaningrat Suryaningrat (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
This research develops a real-time, web-based monitoring and reporting system for production machine repairs to overcome issues found in manual processes, such as delayed handling, limited transparency, and difficulties in tracking repair progress. Using the Extreme Programming (XP) methodology and UML-based system modeling, the system was built with PHP and the Laravel framework to ensure modularity and efficiency. The implemented system improves reporting accuracy, speeds up communication between technicians, admins, and section heads, and enhances oversight of repair activities. The results show that the system increases transparency, streamlines repair management, and contributes to better operational productivity